Prevention models in the fight against HIV/aids - Estrada M., John Harold (Acta Bioethica, 2006)
This article describes three theoretical models to face HIV prevention of transmission in these years. These have been developed sequentially, answering to different prevention views, each one representing a greater inclusion level with respect to the previous one and they are used occasionally in an eclectic way without responding to the particular subject population needs. Finally, the document analyzes some lessons learned.